PENINGKATAN KETERAMPILAN MELALUI PELATIHAN MAKE UP PANGGUNG PADA LEMBAGA GAYATRI BEAUTY ACADEMY DI SINGAPORE - Aniesa Puspa Arum; Supiani, Titin Supiani (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Singapore is a country with a dense population, where the majority of the population are foreigners. One of them is Indonesian migrant workers (domestic workers) because Indonesia is one of the countries that sends its workforce abroad in large numbers. Having additional skills in domestic workers will be an added value forworking in larger companies. The purpose of this service is to increase the knowledge and skills of domesticworkers by providing stage make-up materials. The dedication method is carried out by demonstrations andtraining on stage make-up. Evaluation is assessed using tests and questionnaires. The training was attended by20 domestic workers, the results of the evaluation of the participants' abilities showed that 82% answered thequestions correctly. While the satisfaction of participants from 58% Very Satisfied, 38% Satisfied and 4% QuiteSatisfied. It can be concluded that the results of the Community Service activities were able to improve stagemake-up skills for domestic workers at the Gayatri Beauty Academy Abstrak Singapore merupakan negara dengan jumlah penduduk yang padat, dimana mayoritas penduduknya merupakan warga asing. Salah satunya adalah pekerja migran Indonesia (domestic worker) karena Indonesia merupakan salah satu negara yang mengirimkan tenaga kerjanya keluar negeri dalam jumlah yang besar. Memiliki skill tambahan pada domestic worker akan menjadi nilai tambah untuk bekerja diperusahaan yang lebih besar. Tujuan dari pengabdianini meningkatan pengetahuan dan keterampilan domestic worker dengan pemberian materi tata rias wajah panggung. Metode pengabdian dilakukan demonstrasi dan pelatihan tata rias wajah panggung Pragawati. Evaluasi dinilai menggunakan tes dan kuesioner. Pelatihan diikuti oleh 20 orang domestic worker, hasil evaluasi kemampuan peserta menunjukan 82% menjawab benar soal. Sedangkan kepuasan peserta dari 58% Sangat Puas, 38% Puas dan 4% Cukup Puas. Dapat disimpulkan hasil kegiatan Pengabdian mampu meningkatkan keterampilan tata rias wajah panggung bagi domestic worker di Gayatri Beauty Academy.